1988
DOI: 10.1017/s0022112088003234
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of laminar boundary-layer flow over a flat plate with a compliant surface

Abstract: The problem has been examined using a kinematic model for wall pliability, wherein a kinematic postulation of the wall boundary conditions is made. A form of the normalized wall-displacement and its phase are used as additional parameters in an extended eigenvalue problem. Using this technique the entire gamut of possibilities regarding stability of flow past (normally) pliable walls can be examined, yet without recourse to any specific material properties for the wall. Rather, the results based on the kinemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…In retrospect, it has been found that those two modes form a common future of the mechanism involving a fluid-structure interaction. A first step toward the comprehension of the dynamic of the modes observed experimentally has been offered by Sen and Arora [37]. Using the classification of Carpenter and Garrad [38,39] in which the unstable modes could be classified as solid-based or fluid-based, Sen and Arora [37] found that a powerful instability they termed transitional could be formed by the coalescence of a solid-based unstable mode and a fluid-based unstable mode.…”
Section: Boundary Layer Flowsmentioning
confidence: 99%
“…In retrospect, it has been found that those two modes form a common future of the mechanism involving a fluid-structure interaction. A first step toward the comprehension of the dynamic of the modes observed experimentally has been offered by Sen and Arora [37]. Using the classification of Carpenter and Garrad [38,39] in which the unstable modes could be classified as solid-based or fluid-based, Sen and Arora [37] found that a powerful instability they termed transitional could be formed by the coalescence of a solid-based unstable mode and a fluid-based unstable mode.…”
Section: Boundary Layer Flowsmentioning
confidence: 99%
“…The second boundary condition is found by equating admittance (defined as normal wall velocity divided by pressure acting on the wall) from the fluid side (Y ) and to that of solid side (Y 0 ). Details may be seen in Sen & Arora (1988).…”
Section: Theorymentioning
confidence: 99%
“…Overwhelming evidence, both experimental (see Grosskreutz [8] and Gaster [7] among others) and theoretical work based on linear stability theory (see Carpenter & Garrad [2,3], Sen & Arora [18], Carpenter & Morris [4], Yeo [23], Davies & Carpenter [5] for example), has confirmed that wall compliance can reduce drag forces in fluid motion. As a result, most recent studies have shifted from seeking to establish whether or not compliance reduces drag or delays transition.…”
Section: E57mentioning
confidence: 99%